2013
DOI: 10.1093/schbul/sbt038
|View full text |Cite
|
Sign up to set email alerts
|

Less Structured Movement Patterns Predict Severity of Positive Syndrome, Excitement, and Disorganization

Abstract: Disorganized behavior is a key symptom of schizophrenia. The objective assessment of disorganized behavior is particularly challenging. Actigraphy has enabled the objective assessment of motor behavior in various settings. Reduced motor activity was associated with negative syndrome scores, but simple motor activity analyses were not informative on other symptom dimensions. The analysis of movement patterns, however, could be more informative for assessing schizophrenia symptom dimensions. Here, we use time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 37 publications
5
43
1
1
Order By: Relevance
“…Importantly, abnormalities in these domains are significantly correlated with each other (Lindenmayer, Bernstein-Hyman, & Grochowski, 1994;Walther et al, 2014), and with severity of perceptual organization impairments (reviewed in Phillips & Silverstein, 2003;Silverstein & Keane, 2011). This all suggests that in schizophrenia there is a widespread failure in dynamic, context-sensitive, grouping.…”
Section: Gestalt Groupingmentioning
confidence: 94%
“…Importantly, abnormalities in these domains are significantly correlated with each other (Lindenmayer, Bernstein-Hyman, & Grochowski, 1994;Walther et al, 2014), and with severity of perceptual organization impairments (reviewed in Phillips & Silverstein, 2003;Silverstein & Keane, 2011). This all suggests that in schizophrenia there is a widespread failure in dynamic, context-sensitive, grouping.…”
Section: Gestalt Groupingmentioning
confidence: 94%
“…Actigraphy has demonstrated that continuous assessment of movement allows the extraction of meaningful parameters such as the average diurnal and nocturnal motor activity, the duration of immobility, or the statistical predictability of movement patterns and their relation to clinical features [111-116]. Notably, a measurable disorganization of movement patterns was related to disorganization of complex behavior and positive symptoms in schizophrenia [114]. Actigraphy may also monitor the course of negative symptoms, even across episodes [116, 117].…”
Section: Mapping Symptoms Onto Brain Systems: Empirical Evidence For mentioning
confidence: 99%
“…From a theoretical point of view, we might say that the prototypical schizotaxic LMPs are neuromotor manifestations of the genetically determined schizophrenic process in the brain (involving hypokrisia) rather than being mere consequences from its subjective symptoms and their underlying neurochemical mechanisms. Conversely, the atypical nonschizotaxic LMPs in schizophrenic patients (manifested as either hypolocomotion or hyperlocomotion) might be conceived as due to the psychomotor disturbances, which represent external expressions of the prevailing negative or positive subjective symptoms and their supposedly neurochemical (dopaminergic) brain mechanisms: hypolocomotion being associated with striatal hypodopaminergia and hyperlocomotion—with striatal hyperdopaminergia . From a chronological point of view, the neuromotor LMPs precede the emergence of subjective symptoms, while the psychomotor LMPs appear after them .…”
Section: Psychomotor and Neuromotor Locomotor Abnormalities In Schizomentioning
confidence: 99%
“…As mentioned before, every single schizophrenic patient might combine prototypical schizotaxic LMPs (indicating locomotor ataxia) with atypical nonschizotaxic ones (indicating either hypolocomotion or hyperlocomotion). Evaluating such subclinical combinations of qualitative and quantitative locomotor abnormalities could allow us to make more reliable predictions for more appropriate drug therapy and its more accurate dosage, which might lead to individualized or personalized treatment strategies . On the other hand, the diversity of possible locomotor combinations could explain why the individual reactions to one and the same antipsychotic treatment might vary from patient to patient and why these individual reactions are more predictable by objective evaluation of the patient's motor abnormalities .…”
Section: Translational Implications Of the Objective Locomotor Evaluamentioning
confidence: 99%